2012
DOI: 10.1063/1.4720396
|View full text |Cite
|
Sign up to set email alerts
|

Shape controllable microgel particles prepared by microfluidic combining external ionic crosslinking

Abstract: Alginate microgels with varied shapes, such as mushroom-like, hemi-spherical, red blood cell-like, and others, were generated by combining microfluidic and external ionic crosslinking methods. This novel method allows a continuous fine tuning of the microgel particles shape by simply varying the gelation conditions, e.g., viscosity of the gelation bath, collecting height, interfacial tension. The release behavior of iopamidol-loaded alginate microgel particles with varied morphologies shows significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 34 publications
3
105
0
Order By: Relevance
“…The morphologies of their xerogels further verify these results of Fig. 2 In general, the collection height (h), the distance between the droplets outlet and the liquid surface of the collection bath is also an important parameter for the control of the microgel shape [19]. Fig.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The morphologies of their xerogels further verify these results of Fig. 2 In general, the collection height (h), the distance between the droplets outlet and the liquid surface of the collection bath is also an important parameter for the control of the microgel shape [19]. Fig.…”
Section: Resultssupporting
confidence: 58%
“…As mentioned above, such tailed-shapes were usually obtained in the case of external gelation. It is mainly attributed to the deformation of Na-ALG droplets caused by gravity, interfacial tension, impact and tangential stress when the droplets dripped into a collection bath and passed through the interface of oil and aqueous phases [19,[24][25][26]. In contrast, the spherical Ca-ALG microgels with L/D ratios of almost 1.0 were obtained as shown in Fig.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…6(e)). Hydrogel beads with similar shapes have been reported previously, formed by droplet deformation either at the liquid/liquid interface 45,46 or in microchannels. 47,48 Together with these previous reports, the present study demonstrated the possibility for controlling the droplet shape by utilizing the interfaces in multiphase systems.…”
Section: Control Of Bead Morphologysupporting
confidence: 69%